Effect of roasting on whole grain barnyard millet to the proximate composition, amino acid profile, total phenolic content and antioxidant activity - Mohd, Mazni Syamim; Shafie, Nurul Husna; Ahmad, Fairus; Shafie, Siti Raihanah (Universiti Putra Malaysia Press, 2023)
Introduction: Barnyard millet, an ancient grain that serves as a staple food and a key component of many diets, requires processing before consumption. Roasting is a common processing method that can enhance millet palatability. However, it is important to ensure that the nutritional properties are well preserved. Hence, this study investigated the influence of roasting on the proximate composition, amino acid composition, total phenolic content (TPC) and antioxidant activity of the whole grain barnyard millet sample. Method: The roasted sample of whole grain barnyard millet was roasted in the oven at 110℃ for 10 minutes and used for proximate analysis and amino acid composition. Meanwhile, TPC and DPPH were performed using the ethanol extract of a roasted whole-grain barnyard millet sample. Results: This study found a significant (p<0.05) of 14.22% reduction in moisture content in roasted millet compared to non-roasted millet. The roasted millet sample showed a higher fat content (p<0.05) compared to the non-roasted millet sample, with values of 5.08±0.24% and 4.38±0.24%, respectively. The total amino acid content of the non-roasted sample was 116.76±11.31ng, while the roasted sample had a value of 123.51±0.23.22ng. In addition, the TPC and antioxidant activity were found significantly higher (p<0.05) in the roasted sample than in the non-roasted sample of whole grain barnyard millet. Conclusion: The roasting method should be considered in processing of the whole grain barnyard millet to enhance the nutrient composition and boost its functionality.